Do global ao local: a hotelaria e a gestão de recursos humanos sustentável - Barros, Lyvia Camila Fernandes Madruga (2022)
In response to growing public awareness of the importance of organizational contributions to sustainable development, there is a greater incentive for companies to report on their sustainability activities. In parallel with this, there has been the development of Sustainable Human Resource Management, which encompasses a growing body of professional and academic literature connecting notions of corporate sustainability to Human Resource Management. The general objective of this work was to analyze the adoption of sustainable human resources management practices in the tourism sector and its impact on employees. For this, specific objectives were outlined, which helped in the general conduct of the work, namely: Propose an integrative concept for sustainable human resources management; Identify the main sustainable practices in the context of human resources management developed by the largest hotel chains in the world; Describe the sustainable human resources management practices developed by leading hotels in Brazil; Investigate the applicability of sustainable human resources management practices in small businesses in a destination focused on sustainable tourism and analyze the impact of sustainable human resources management practices in relation to employees. As a methodological contribution, the research was developed through qualitative analysis, being distributed in three stages: The first stage called global, with analysis of the sustainability reports of the ten largest hotel chains in the world. Second stage called national, investigating through the Booking.com report two best-rated sustainable hotels in Brazil, through interviews with managers and the third and last stage called local, with a qualitative approach, in-depth interview and group holding focal point, with the Chã de Jardim Community – Areia (PB). As a result, the thesis proposal led to a systematic review of the literature, providing an overview of the academic productions that served as a basis for the construction of an integrating concept, the practices developed by the great hotel chains in the world, were mapped and through the analyzes, it was identified that the actions are developed in a broad way, being replicated in all hotel units of the brand distributed in the continents. From a national perspective, the practices of two hotels were studied – Botanique Spa and Lapinha Spa, where, through interviews with human resources managers, the practices and their operations within the company were listed. And finally, the local analysis, being carried out through an in-depth interview with the entrepreneur - Luciana Balbino and the realization of the focus group, with the participation of the company's employees, it was verified how the practices impact the lives of the employees. Through the results, the thesis shows that despite the differences in resources, the practices developed at the local level are directed to the needs of employees and thus manage to cover all the pillars of the integrative concept of Sustainable Human Resource Management.